Accountability of Parking Levy Revenue to Local Revenue of Sinjai Regency - Syamsiah Hasyim; Mukrimah, Mukrimah; Jusniati, Jusniati; Sofyang, Sofyang; Mahdi T (Tinta Emas Institute, 2023)
This study aims to determine the accountability of acceptance of parking fees to the Regional Original Revenue of Sinjai Regency. The research methodology uses a qualitative type, data collection techniques are observation, interviews and documentation. Data analysis techniques of data collection, data reduction, data presentation and drawing conclusions. The results of the research on the accountability of parking retribution receipts to the Sinjai District's Original Revenue have been implemented but not yet maximized. Transparency has not been maximized, this has happened because there has been no public information delivery regarding receipt of parking fees. While accountability has been carried out maximally, this is evidenced by carrying out accountability with a manual model where tickets distributed must be paid for in money and existing tickets must be accounted for or cannot be eliminated. Control of acceptance of parking fees has been carried out optimally with controls at the point of collection of fees. Responsibilities have been carried out to the fullest with the existence of these regulations consisting of Regent Regulation number 7 of 2022 concerning Adjustment of Retribution Rates and Regional Regulation number 16 of 2012 Concerning Special Parking Place Retribution. While responsiveness has been implemented but not optimal, this happens because the targets set are sometimes not achieved.